Implementation of Islamic sharia in Banten from the perspective of Nahdlatul Ulama students - Agnia Dwi Rahma (Jurnal Penelitian Humaniora, 2026)
This study explores how students from Nahdlatul Ulama (NU), particularly those involved in the Indonesian Islamic Student Movement (PMII), view the discourse surrounding the implementation of Islamic law (sharia) in Banten Province, as well as the factors that shape their perspectives. This research employed a qualitative approach with a descriptive-analytical design. The data were collected from six students affiliated with NU/PMII in Banten, selected through purposive sampling based on specific criteria. Data collection instruments included in-depth interviews, observation, documentation, and questionnaires to ensure comprehensive data. Data analysis followed the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that respondents interpret Islamic law in a comprehensive manner, encompassing aspects of worship, morality, and social relations, rather than limiting it to formal legal frameworks. The majority of respondents reject the formalization of sharia into state law and instead emphasize a substantive approach grounded in the values of justice and public welfare. Their perspectives tend to be cautious, contextual, and responsive to the realities of a pluralistic society, with NU’s principles of religious moderation, such as tawassuth (moderation) and tasamuh (tolerance), play a significant role in shaping inclusive and non-coercive views, as well as in rejecting the politicization of religion in order to maintain national unity.